Preparation method of lithium / sodium doped gallium nitride, lithium / sodium doped gallium nitride and application

Through the preparation method of lithium/sodium doped gallium nitride, the problem of lower capacitance of existing gallium nitride materials is solved, and the specific capacitance is improved and the electrochemical performance is significantly enhanced.

CN119409144APending Publication Date: 2025-02-11QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411558796.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing gallium nitride materials have lower specific capacitance in the field of electrochemical capacitors, which limits their application, and the doping methods of transition metals and lanthanides are complex and costly.

Method used

The preparation method of lithium/sodium doped gallium nitride is adopted, and the preparation of lithium/sodium doped gallium nitride is achieved through the carbon-heat reduction reaction using gallium trichloride, melamine, lithium nitrate or sodium nitrate as raw materials.

Benefits of technology

Lithium/sodium doped gallium nitride has a large specific surface area and total pore capacity, narrowing the energy band, and the center of the d-band is closer to the Fermi level, which significantly enhances its electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409144A_ABST
    Figure CN119409144A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of lithium / sodium doped gallium nitride, lithium / sodium doped gallium nitride and application, the preparation method comprises the following steps: S1, melamine, a benzene solution of gallium trichloride and lithium nitrate or sodium nitrate are ground and mixed to obtain a mixture A, n (melamine) = n (gallium trichloride) + n (lithium nitrate or sodium nitrate), and n represents the amount of substance; s2, transferring the mixture A into a reaction furnace, heating the reaction furnace to 800 DEG C under the protection of gas, keeping the temperature for 6 hours, and naturally cooling to room temperature to obtain a solid B; and S3, washing and drying the solid B to obtain the lithium / sodium doped gallium nitride powder. According to the preparation method of the lithium / sodium-doped gallium nitride, regulation and control of the macrostructure and the microstructure of the lithium / sodium-doped gallium nitride are realized by controlling the molar ratio of gallium trichloride to lithium nitrate or gallium trichloride to sodium nitrate, the preparation method is simple and reliable, and the effect of improving the interface energy storage of the gallium nitride is remarkable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrode material preparation and electrochemical energy storage, and relates to a preparation method of lithium / sodium doped gallium nitride, lithium / sodium doped gallium nitride and application thereof. Background Art

[0002] Gallium nitride (GaN) has a wide adjustable band gap, high photoelectron conductivity and excellent chemical stability, and has been widely used in light-emitting diodes, photodetectors, field-effect transistors, sensors, power electronic devices, and energy storage and conversion systems. As an electrode material for interfacial energy storage, GaN exhibits excellent rate performance, but low specific capacitance (Advanced Materials 2016, 28(19), 3768-3776), which limits its practical application in the field of electrochemical capacitors (supercapacitors).

[0003] For GaN, many studies have reported that doping with transition metals and lanthanides can improve its optical, electronic, ferromagnetic, rare-earth magnetic semiconductor, gas adsorption, photocatalytic and mechanical properties. However, research on improving GaN interface energy storage by doping with metal elements has not been reported. In addition, doping with transition metals and lanthanides is usually achieved by hydride vapor phase epitaxy or magnetron sputtering, which involves expensive equipment, reagents and consumables, and the method is complicated and costly. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a preparation method of lithium / sodium-doped gallium nitride, lithium / sodium-doped gallium nitride and application thereof. The method is simple and reliable. The lithium / sodium-doped gallium nitride has a large specific surface area and total pore volume, and has a narrowed energy band, and the d-band center is closer to the Fermi level, and has significantly enhanced electrochemical performance.

[0005] A method for preparing lithium / sodium-doped gallium nitride, using gallium trichloride as a gallium source, melamine as a nitrogen source, lithium nitrate or sodium nitrate as a dopant, and obtaining a target product through a carbothermal reduction reaction.

[0006] A method for preparing lithium / sodium doped gallium nitride, comprising the following steps:

[0007] a. Grind and mix melamine, a benzene solution of gallium trichloride and lithium nitrate or sodium nitrate in a fume hood in a certain ratio to obtain a mixture A.

[0008] b. Transfer mixture A to a crucible and then to a tube furnace.

[0009] c. Raise the temperature of the tube furnace to 800°C under nitrogen or argon protection, keep it warm for 6 hours, and naturally cool to room temperature to obtain solid B.

[0010] d. The solid B is thoroughly washed with distilled water and dried to obtain lithium / sodium-doped gallium nitride powder.

[0011] In step a, the melamine, gallium trichloride and lithium nitrate or sodium nitrate are prepared, wherein n(melamine)=n(gallium trichloride)+n(lithium nitrate or sodium nitrate), and n represents the amount of the substance.

[0012] The benzene solution of gallium trichloride in step a uses benzene to dissolve gallium chloride for easy use, and there is no particular limitation on the concentration of the solution.

[0013] The gallium trichloride and lithium nitrate or sodium nitrate described in step a, wherein the molar ratio of gallium trichloride to lithium nitrate or gallium trichloride to sodium nitrate is (90-97.5):(10-2.5).

[0014] The crucible in step b includes but is not limited to a ceramic crucible, a corundum crucible and a boron nitride crucible.

[0015] The heating rate in step c is 2-10°C min -1 .

[0016] The drying in step d, wherein the drying temperature is 60-100° C. and the drying time is 4-12 h.

[0017] The present invention also provides lithium / sodium doped gallium nitride powder prepared by the above method.

[0018] The present invention also provides an application of the lithium / sodium doped gallium nitride powder for use as an electrode material for a working electrode of a supercapacitor.

[0019] The present invention also provides a method for preparing a working electrode of lithium / sodium-doped gallium nitride powder prepared by the above method, comprising the following steps:

[0020] Take appropriate amounts of lithium / sodium-doped gallium nitride powder, acetylene black and polyvinylidene fluoride, the mass ratio of which is 8:1:1, transfer them to an agate mortar, drop appropriate amounts of N-methylpyrrolidone, grind them thoroughly, and prepare a slurry;

[0021] The slurry was evenly coated on the current collector (stainless steel wire mesh or carbon cloth), and then placed in a vacuum drying oven and dried at 80° C. for 12 h to obtain a working electrode.

[0022] The lithium / sodium doped gallium nitride working electrode, wherein the loading amount of lithium / sodium doped gallium nitride (active material) is 2.5-10 mg cm -2 .

[0023] Beneficial Effects

[0024] 1. The present invention provides a method for preparing lithium / sodium-doped gallium nitride, which uses gallium trichloride as a gallium source, melamine as a nitrogen source, and lithium nitrate or sodium nitrate as a dopant. The decomposition products of lithium nitrate or sodium nitrate, lithium oxide or sodium oxide, are used to react with gallium nitride in a carbon thermal reduction environment to prepare lithium / sodium-doped gallium nitride by solid phase reaction at a relatively low reaction temperature, thereby providing a simple method for mass production of lithium / sodium-doped gallium nitride.

[0025] 2. The preparation method of lithium / sodium-doped gallium nitride provided by the present invention uses lithium nitrate and sodium nitrate as dopants to improve the crystal strength of gallium nitride samples. The doping of lithium and sodium will cause gallium nitride to produce lattice tension, resulting in lattice deformation and improving its electrochemical properties.

[0026] 3. A preparation method of lithium / sodium doped gallium nitride provided by the present invention: With the increase of the amount of lithium nitrate and sodium nitrate, the doping concentration of lithium and sodium in gallium nitride gradually increases, the nanostructure on the surface of gallium nitride particles (4-8 μm) gradually disappears, and finally the surface of the particles becomes smoother; at the same time, with the increase of lithium / sodium doping concentration, the specific surface area (S BET ), micropore surface area (S micropore ) and total pore volume (V total pore ) also changes accordingly. The specific surface area and total pore volume of lithium / sodium doped gallium nitride are significantly increased compared with undoped gallium nitride, especially when the molar ratio of gallium trichloride to lithium nitrate or sodium nitrate is 95:5. The increase in specific surface area and total pore volume can increase more active sites and shorten the ion transport path, which is beneficial to improve the electrochemical performance of the sample electrode.

[0027] 4. The lithium / sodium-doped gallium nitride prepared by the preparation method provided by the present invention not only has a large specific surface area and total pore volume, but also has a narrowed energy band and a d-band center closer to the Fermi level, which is beneficial to improving its surface reaction activity and increasing its affinity with electrolyte ions, thereby improving the charge storage capacity and having significantly enhanced electrochemical properties.

[0028] 5. By utilizing the technical solution provided by the present invention, by controlling the molar ratio of gallium trichloride to lithium nitrate or gallium trichloride to sodium nitrate, not only the macroscopic properties of gallium nitride can be regulated, but also its microstructure can be adjusted.

[0029] 6. The working electrode prepared from the lithium / sodium doped gallium nitride powder of the present invention has a loading amount of lithium / sodium doped gallium nitride (active material) of 2.5-10 mg cm -2 , with excellent electrochemical performance. At a current density of 0.5A g -1 The discharge capacity can reach 160-188F g -1; When the current density increases to 100A g -1 When the capacity retention rate is higher than 65%, the lithium / sodium doped gallium nitride working electrode has a relatively high volumetric capacity, which is much higher than that of electrode materials such as carbon materials and other metal nitrides.

[0030] 7. Symmetrical electrochemical capacitor based on lithium / sodium doped gallium nitride at 10 mA cm -2 After 20,000 cycles, the capacity retention rate is higher than 94%. Moreover, it can maintain good electrochemical properties at -60℃ and 120℃, and has high specific energy-specific power performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 XRD patterns of the samples: (a) XRD pattern comparison between lithium-doped GaN and undoped GaN; (b) XRD pattern comparison between sodium-doped GaN and undoped GaN.

[0032] Figure 2 SEM images of samples: (a) S-1; (b) S-2; (c) S-3; (d) S-4; (e) S-5; (f) S-6.

[0033] Figure 3 High-resolution TEM images (ac) and element distribution maps (df) of sample S-5.

[0034] Figure 4 Electrochemical performance of the sample working electrode in a three-electrode system: (a) Li-doped GaN at 10 mV s -1 Cyclic voltammetry curves under 10 mV s -1 Cyclic voltammetry curves under 0.5Ag; (c) Li-doped GaN -1 (d) constant current charge-discharge curves of sodium-doped GaN at 0.5Ag -1 (e) Li-doped GaN at 100A g -1 (f) Constant current charge and discharge curves of sodium-doped GaN at 100Ag -1 (g) The rate curve of Li-doped GaN; (h) The rate curve of Na-doped GaN; The electrolyte is 1M H2SO4, and the loading amount of active material on the working electrode is 2.5mg cm -2 .

[0035] Figure 5Electrochemical performance of WE-2 and WE-5 based symmetrical electrochemical capacitors at room temperature: (a) Cyclic voltammetry curves of WE-2 based devices at different scan rates; (b) Cyclic voltammetry curves of WE-5 based devices at different scan rates; (c) Constant current charge-discharge curves of WE-2 based devices at different current densities; (d) Constant current charge-discharge curves of WE-5 based devices at different current densities; (e) Rate curves of WE-2 and WE-5 based devices; (f) Cyclic voltammetry curves of WE-2 and WE-5 based devices at 10 mA cm -2 The cycling curve under the condition of ; the electrolyte is a phosphoric acid-water-dimethyl sulfoxide mixture, wherein the mass fraction of phosphoric acid in the electrolyte is 52wt%, water and dimethyl sulfoxide are mixed solvents, and the volume ratio of water to dimethyl sulfoxide is 9:1; the loading amount of active material on the single electrode is 10mg cm -2 . DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below through specific embodiments in combination with the accompanying drawings. These embodiments are only for illustrating the technical solution of the present invention and cannot be regarded as limiting the content of the claims of the present invention.

[0037] Benzene and N-methylpyrrolidone in the examples were purchased from Shanghai Sinopharm Chemical Reagent Co., Ltd.; stainless steel mesh, carbon cloth, acetylene black, and polyvinylidene fluoride were purchased from Taobao Jinghong New Energy; BH5510 sulfonated diaphragm was purchased from Shenzhen Gebang Technology Co., Ltd.; gallium trichloride was homemade by the combustion reaction of metallic gallium and chlorine.

[0038] The X-ray powder diffraction spectrum (XRD) was obtained by using a German Bruker D8 Advance powder diffractometer; the scanning electron microscope (SEM) photos and element distribution diagrams were obtained by using a Japanese Hitachi Regulus8220 field emission scanning electron microscope; the transmission electron microscope (TEM) photos were obtained by using a US FEI Talos F200X high-resolution transmission electron microscope; the nitrogen adsorption-desorption isotherms and pore size distribution were obtained by using a US micromeritics ASAP 2460 fully automatic specific surface area and pore size analyzer; the metal element content was obtained by using a US PerkinElmer Avio200 inductively coupled plasma optical emission spectrometer (ICP-OES).

[0039] Theoretical calculations were performed based on density functional theory using the VASP (Vienna ab initio simulationpackage) program and the projected augmented plane wave method based on the generalized gradient approximation.

[0040] The electrochemical performance of the working electrode and supercapacitor device was obtained by Shanghai Chenhua CHI760E electrochemical analyzer. The active material loading of the sample electrode was 2.5-10 mg cm -2 , the current collector is stainless steel mesh or carbon cloth; in the three-electrode system, the counter electrode is platinum, the reference electrode is Hg / Hg2SO4, and the electrolyte is 1 mol L -1 H2SO4; in the two-electrode system, the electrolyte is a mixture of phosphoric acid-water-dimethyl sulfoxide, and the diaphragm is a BH5510 type sulfonated diaphragm.

[0041] Example 1

[0042] A method for preparing lithium-doped gallium nitride, comprising the following steps:

[0043] a. Mix 4mmol melamine, 3.9mL 1mol L -1 GaCl3-benzene solution and 0.1mmol lithium nitrate were ground and mixed in a fume hood to obtain mixture A.

[0044] b. Transfer mixture A to a corundum crucible and then transfer to a tube furnace.

[0045] c. Heat the tube furnace to 800°C under nitrogen protection at a rate of 2°C min -1 , keep warm at 800℃ for 6h, cool naturally to room temperature to obtain solid B.

[0046] d. Wash solid B with distilled water and dry at 60°C for 12 h to obtain sample S-1.

[0047] Example 2

[0048] A method for preparing lithium-doped gallium nitride, comprising the following steps:

[0049] a. Mix 4mmol melamine, 3.8mL 1mol L -1 GaCl3-benzene solution and 0.2mmol lithium nitrate were ground and mixed in a fume hood to obtain mixture A.

[0050] b. Transfer mixture A to a corundum crucible and then transfer to a tube furnace.

[0051] c. Heat the tube furnace to 800°C under nitrogen protection at a rate of 2°C min -1 , keep warm at 800℃ for 6h, cool naturally to room temperature to obtain solid B.

[0052] d. Wash solid B with distilled water and dry at 60°C for 12 h to obtain sample S-2.

[0053] Example 3

[0054] A method for preparing lithium-doped gallium nitride, comprising the following steps:

[0055] a. Mix 4mmol melamine, 3.6mL 1mol L -1 GaCl3-benzene solution and 0.4 mmol lithium nitrate were ground and mixed in a fume hood to obtain mixture A.

[0056] b. Transfer mixture A to a corundum crucible and then transfer to a tube furnace.

[0057] c. Heat the tube furnace to 800°C under nitrogen protection at a rate of 2°C min -1 , keep warm at 800℃ for 6h, cool naturally to room temperature to obtain solid B.

[0058] d. Wash solid B with distilled water and dry at 60°C for 12 h to obtain sample S-3.

[0059] Example 4

[0060] A method for preparing sodium-doped gallium nitride, comprising the following steps:

[0061] a. Mix 4mmol melamine, 3.9mL 1mol L -1 GaCl3-benzene solution and 0.1mmol sodium nitrate were ground and mixed in a fume hood to obtain mixture A.

[0062] b. Transfer mixture A to a corundum crucible and then transfer to a tube furnace.

[0063] c. Heat the tube furnace to 800°C under nitrogen protection at a rate of 10°C min -1 , keep warm at 800℃ for 6h, cool naturally to room temperature to obtain solid B.

[0064] d. Wash solid B with distilled water and dry at 60°C for 6 h to obtain sample S-4.

[0065] Example 5

[0066] A method for preparing sodium-doped gallium nitride, comprising the following steps:

[0067] a. Mix 4mmol melamine, 3.8mL 1mol L -1 GaCl3-benzene solution and 0.2mmol sodium nitrate were ground and mixed in a fume hood to obtain mixture A.

[0068] b. Transfer mixture A to a corundum crucible and then transfer to a tube furnace.

[0069] c. Heat the tube furnace to 800°C under nitrogen protection at a rate of 10°C min-1 , keep warm at 800℃ for 6h, cool naturally to room temperature to obtain solid B.

[0070] d. Wash solid B with distilled water and dry at 60°C for 6 h to obtain sample S-5.

[0071] Example 6

[0072] A method for preparing sodium-doped gallium nitride, comprising the following steps:

[0073] a. Mix 4mmol melamine, 3.6mL 1mol L -1 GaCl3-benzene solution and 0.4mmol sodium nitrate were ground and mixed in a fume hood to obtain mixture A.

[0074] b. Transfer mixture A to a corundum crucible and then transfer to a tube furnace.

[0075] c. Heat the tube furnace to 800°C under nitrogen protection at a rate of 10°C min -1 , keep warm at 800℃ for 6h, cool naturally to room temperature to obtain solid B.

[0076] d. Wash solid B with distilled water and dry at 60°C for 6 h to obtain sample S-6.

[0077] Comparative Example 1

[0078] A method for preparing gallium nitride powder, comprising the following steps:

[0079] a. Mix 4mmol melamine with 4mL 1mol L -1 The GaCl3-benzene solution was ground and mixed in a fume hood to obtain mixture A.

[0080] b. Transfer mixture A to a corundum crucible and then transfer to a tube furnace.

[0081] c. Heat the tube furnace to 800°C under nitrogen protection at a rate of 10°C min -1 , keep warm at 800℃ for 6h, cool naturally to room temperature to obtain solid B.

[0082] d. Wash solid B with distilled water and dry at 60°C for 12 h to obtain sample S-0.

[0083] Example 7

[0084] A method for preparing a lithium-doped gallium nitride working electrode, comprising the following steps:

[0085] a. Take an appropriate amount of S-1 powder, acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1, transfer to an agate mortar, add an appropriate amount of N-methylpyrrolidone, grind thoroughly, and obtain a slurry;

[0086] b. The slurry was evenly coated on a stainless steel wire mesh, and then placed in a vacuum drying oven and dried at 80 °C for 12 h to obtain a working electrode WE-1. The GaN loading on the working electrode was 2.5 mg cm -2 .

[0087] c. 1 mol L -1 H2SO4 was used as the electrolyte, a metal platinum sheet was used as the counter electrode, and a Hg / Hg2SO4 electrode was used as the reference electrode to test the electrochemical properties of the working electrode.

[0088] Example 8

[0089] A method for preparing a lithium-doped gallium nitride working electrode, comprising the following steps:

[0090] The S-1 powder was replaced with S-2, and the remaining operations were the same as in Example 7 to obtain a working electrode WE-2.

[0091] Example 9

[0092] A method for preparing a lithium-doped gallium nitride working electrode, comprising the following steps:

[0093] The S-1 powder was replaced with S-3, and the remaining operations were the same as in Example 7 to obtain a working electrode WE-3.

[0094] Example 10

[0095] A method for preparing a sodium-doped gallium nitride working electrode, comprising the following steps:

[0096] The S-1 powder in Example 7 was replaced with S-4, and the remaining operations were the same to obtain a working electrode WE-4.

[0097] Embodiment 11

[0098] A method for preparing a sodium-doped gallium nitride working electrode, comprising the following steps:

[0099] The S-1 powder in Example 7 was replaced with S-5, and the remaining operations were the same to obtain a working electrode WE-5.

[0100] Example 12

[0101] A method for preparing a sodium-doped gallium nitride working electrode, comprising the following steps:

[0102] The S-1 powder in Example 7 was replaced with S-6, and the remaining operations were the same to obtain a working electrode WE-6.

[0103] Comparative Example 2

[0104] A method for preparing a gallium nitride working electrode, comprising the following steps:

[0105] The S-1 powder in Example 7 was replaced with S-0, and the remaining operations were the same to obtain a working electrode WE-0.

[0106] Example 13

[0107] A lithium-doped gallium nitride-based symmetrical supercapacitor is assembled in the following steps:

[0108] a. Take an appropriate amount of S-2 powder, acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1, transfer to an agate mortar, add an appropriate amount of N-methylpyrrolidone, grind thoroughly, and obtain a slurry;

[0109] b. The slurry was evenly coated on a stainless steel wire mesh, and then placed in a vacuum drying oven and dried at 80°C for 12 h to obtain a working electrode with an active material loading of 10 mg cm -2 .

[0110] c. Using a phosphoric acid-water-dimethyl sulfoxide mixture as the electrolyte, a BH5510 type sulfonated diaphragm is selected, and an R2032 type button-type symmetrical supercapacitor is assembled; wherein the mass fraction of phosphoric acid in the electrolyte is 52wt%, water and dimethyl sulfoxide are the mixed solvents, and the volume ratio of water to dimethyl sulfoxide is 9:1.

[0111] Embodiment 14

[0112] The steps of assembling a sodium-doped gallium nitride-based symmetrical supercapacitor are as follows:

[0113] The S-2 powder in Example 13 was replaced with S-5, and the rest was the same as Example 13.

[0114] Results Analysis

[0115] Figure 1 a and Figure 1 b are the XRD patterns of lithium-doped and sodium-doped GaN samples, respectively. Figure 1 a and Figure 1 The positions of the crystal plane diffraction peaks marked in b are in good agreement with the positions of the crystal planes of hexagonal wurtzite gallium nitride (PDF#50-0792), proving the formation of gallium nitride. In addition, the intensities of the crystal plane diffraction peaks of samples S-1 to S-6 are all higher than those of S-0, indicating that the use of lithium nitrate and sodium nitrate as dopants can improve the crystal strength of gallium nitride samples; this is attributed to the fact that the reaction of nitrate with melamine during the carbon thermal reduction process is an exothermic reaction, which can contribute additional energy to the reaction system.

[0116] Table 1 ICP-OES test results of samples

[0117]

[0118] The presence of Li and Na in lithium-doped and sodium-doped samples is supported by ICP-OES test results (Table 1). As can be seen from Table 1, with the increase in the amount of lithium nitrate and sodium nitrate, the doping concentration of lithium and sodium in the sample gradually increases; but it should be pointed out that the Li / Ga and Na / Ga atomic ratios detected by ICP-OES are both smaller than the molar ratios of lithium nitrate / gallium chloride and sodium nitrate / gallium chloride during the experiment, which indicates that not all lithium and sodium can be doped into the gallium nitride matrix.

[0119] By changing the molar ratio of gallium trichloride to lithium nitrate or sodium nitrate, the morphology and texture characteristics of the sample can be controlled. As the lithium / sodium doping concentration increases, the nanostructure on the surface of the gallium nitride particles (4-8μm) gradually disappears, and eventually the particle surface becomes smoother ( Figure 2 ).

[0120] At the same time, with the increase of lithium / sodium doping concentration, the specific surface area (S BET ), micropore surface area (S micropore ) and total pore volume (V total pore ) also changes accordingly (Table 2). As can be seen from Table 2, compared with the undoped GaN S-0, the specific surface area and total pore volume of the Li / Na doped GaN samples are significantly increased. The increase in specific surface area and total pore volume can increase more active sites and shorten the ion transport path, which is beneficial to improve the electrochemical performance of the sample electrode.

[0121] Table 2 Texture characteristics of samples

[0122]

[0123] Lithium / sodium doped GaN is not only verified by XRD and ICP-OES results, but also supported by high-resolution TEM and element distribution test results. Taking sodium doped GaN sample S-5 as an example ( Figure 3 ), the lattice fringes with interplanar spacing of 0.236 and 0.264 nm correspond to the (101) and (002) planes of wurtzite GaN, respectively ( Figure 3 ac). Compared with the GaN reference (PDF#50-0792), the (101) plane spacing of S-5 shrinks and the (002) plane spacing expands; this indicates that sodium doping will cause lattice tension in GaN, resulting in lattice deformation. The same situation will also occur in lithium-doped GaN. The element distribution diagram shows that the sample is sodium-doped GaN ( Figure 3 d,e), and the sodium element is evenly distributed in the GaN matrix ( Figure 3 f).

[0124] Figure 4 The electrochemical performance of the sample working electrode in three-electrode mode was demonstrated. Figure 4 a and 4b are cyclic voltammetry (CV) curves of lithium-doped gallium nitride working electrode and sodium-doped gallium nitride working electrode, respectively, where the undoped gallium nitride WE-0 working electrode is used as a comparison. Figure 4 As can be seen from a and 4b, the CV curves are both rectangular, indicating that the charge storage of lithium / sodium doped GaN is similar to WE-0, and the electrochemical double layer capacitor is the main source of charge storage. The difference is that the CV curve area of ​​WE-0 is relatively small, which means that the specific capacity of lithium / sodium doped GaN is higher than that of WE-0. The specific capacity of the working electrode can be calculated from its constant current charge and discharge curve ( Figure 4 cf). At 0.5A g -1 Under this condition, the discharge capacity of WE-0 is 70F g -1 The discharge specific capacities of lithium-doped gallium nitride WE-1, WE-2, and WE-3 are 85, 160, and 90 F g, respectively. -1 The discharge specific capacities of sodium-doped GaN WE-4, WE-5, and WE-6 are 123, 188, and 130 F g, respectively. -1 When the current density increases to 100Ag -1 When the discharge capacity of WE-1, WE-2, WE-3, WE-4, WE-5 and WE-6 is 58, 109, 64, 85, 131 and 85 F g, respectively. -1 , higher than WE-0's 49F g -1 From 0.5 to 200A g -1 In the range, the specific capacity of Li / Na doped GaN is higher than that of undoped GaN WE-0( Figure 4 g,h). Li / Na doped GaN has a high rate capability, which is not only reflected in the high rate capability when the current density increases from 0.5 to 100A g -1 (expanded 200 times) the capacity retention rate is higher than 65%, which is also reflected in 100A g -1 The charge and discharge curves under the condition still maintain good symmetry ( Figure 4 e,f).

[0125] The packing densities of Li / Na-doped GaN working electrodes are 2.837 and 2.868 g cm, respectively. -3 Therefore, the Li / Na-doped GaN working electrode has a relatively high volumetric capacity. For example, at 0.5 and 200 A g -1 Under the condition of 1.5 % RH, the discharge specific capacities of WE-2 and WE-5 working electrodes are 454, 539, 238 and 298 F cm-1, respectively. -3The volumetric capacity of lithium / sodium-doped gallium nitride is much higher than that of electrode materials such as carbon materials and other metal nitrides.

[0126] The present invention also provides application in lithium / sodium doped gallium nitride based symmetrical electrochemical capacitors (ie supercapacitors).

[0127] Considering that WE-2 and WE-5 have higher specific capacity, the present invention selects WE-2 and WE-5 as working electrodes, and uses phosphoric acid-water-dimethyl sulfoxide mixed solution as electrolyte, wherein the mass fraction of phosphoric acid in the electrolyte is 52wt%, water and dimethyl sulfoxide are mixed solvents, and the volume ratio of water to dimethyl sulfoxide is 9:1, and symmetrical electrochemical capacitor devices are assembled respectively. In order to meet the requirements of commercial electrochemical capacitors for electrode loading (not less than 10mg cm -2 ), the loading amount of active materials on WE-2 and WE-5 electrodes is 10 mg cm -2 . Figure 5 The electrochemical performances of WE-2∥WE-2 and WE-5∥WE-5 devices at room temperature are demonstrated.

[0128] Figure 5 a and 5b are the CV curves of the two devices. The CV of the two devices is at 200mV s -1 The good rectangular shape can be maintained at a high scanning rate, indicating that even at a loading of 10 mg cm -2 Under the condition of , WE-2 and WE-5 can show good rate performance. The good rate performance of WE-2 and WE-5 is verified by the constant current charge and discharge curve ( Figure 5 c, d). That is, at 50 mA cm -2 The constant current charge and discharge curves of the two devices still maintain good symmetry. -2 Under the condition of WE-2∥WE-2 and WE-5∥WE-5, the discharge specific capacities of the devices are 163 and 194 mF cm, respectively. -2 Lower; relative to 1mA cm -2 , the capacity retention rates were 45.4% and 48.1% respectively ( Figure 5 e). At 10 mA cm -2 After 20,000 cycles, the discharge specific capacities of WE-2∥WE-2 and WE-5∥WE-5 devices remained at 251 and 283 mF cm, respectively. -2 , the capacity retention rates are 94.4% and 94.6% respectively ( Figure 5 f).

[0129] In addition, the WE-5∥WE-5 device can maintain good electrochemical performance at -60℃ and 120℃. The output voltage of the device is 2.4V at -60℃ and 1V at 120℃. The device can maintain good electrochemical performance at 1-10 and 2-50mA cm at -60 and 120℃, respectively. -2 At -60℃ 1mA cm -2 The device has a discharge capacity of 200 mF cm -2 . At 120℃ 2mA cm -2 The device has a discharge capacity of 418 mF cm -2 . At -60℃ 5mA cm -2 After 20,000 cycles, the device’s capacity retention rate is 100% at 120℃50mA cm -2 After 20,000 cycles, the capacity retention rate of the device was 88.4%.

[0130] WE-2∥WE-2 and WE-5∥WE-5 devices have high specific energy-specific power performance. At room temperature, the specific energy of WE-2∥WE-2 device is 31.8mW h cm -3 , corresponding to a specific power of 215 mW cm -3 ; The specific energy of WE-5∥WE-5 device is 36.1mW h cm -3 , corresponding to a specific power of 215 mW cm -3 At -60°C, the specific energy of the WE-5∥WE-5 device is 45.9 mW h cm -3 , corresponding to a specific power of 344 mW cm -3 At 120°C, the specific energy of the WE-5∥WE-5 device is 16.7 mW h cm -3 , corresponding to a specific power of 287 mW cm -3 .

[0131] In addition to the relatively high specific surface area and total pore volume (Table 2), the excellent electrochemical properties of the Li / Na-doped GaN working electrode are attributed to the Li + / Na +Adjustment of GaN microstructure by doping. Taking S-2 and S-5 as examples, theoretical calculation results show that: (1) Compared with S-0, the energy bands of S-2 and S-5 are reduced by 0.39 and 0.18 eV respectively. The reduction of the energy bands of S-2 and S-5 is conducive to improving the electron migration ability, thereby improving its rate performance; (2) The d-band centers of S-0, S-2 and S-5 are 2.743, 0.727 and 2.604 eV respectively. Compared with S-0, the d-band centers of S-2 and S-5 are closer to the Fermi level, which is conducive to improving the surface reaction activity of S-2 and S-5, increasing the affinity with the electrolyte ions, and thus improving the charge storage capacity.

[0132] In summary, the present invention provides a method for preparing lithium / sodium doped gallium nitride, lithium / sodium doped gallium nitride and its application in the field of electrochemical energy storage. Lithium and sodium doping can not only regulate the macrostructure of gallium nitride, but also adjust the microstructure of gallium nitride, thereby significantly improving the interfacial energy storage characteristics of gallium nitride. Symmetrical electrochemical capacitors based on lithium / sodium doped gallium nitride have excellent specific energy-specific power performance and can operate reliably in a wide temperature range of -60-120°C.

Claims

1. A method for preparing lithium-doped gallium nitride, characterized in that: The following steps are involved: S1, grinding and mixing melamine, a benzene solution of gallium trichloride and lithium nitrate in a fume hood to obtain a mixture A-1, wherein n(melamine)=n(gallium trichloride)+n(lithium nitrate), n represents the amount of substance, and the amount ratio of gallium trichloride to lithium nitrate is (90-97.5):(10-2.5); S2, transferring the mixture A-1 to a crucible, and then transferring it to a tube furnace; S3, heating the tube furnace to 800°C under nitrogen or argon protection, keeping the temperature for 6 hours, and naturally cooling to room temperature to obtain solid B-1; S4, washing the solid B-1 with distilled water and drying it to obtain lithium-doped gallium nitride powder.

2. The method for preparing lithium-doped gallium nitride according to claim 1, characterized in that: In step S1, the molar ratio of gallium trichloride to lithium nitrate is 95:

5.

3. The method for preparing lithium-doped gallium nitride according to claim 1 or 2, characterized in that: In step S3, the heating rate of the tube furnace is 2-10°C min -1 ; In step S4, the drying temperature is 60-100°C and the drying time is 4-12h.

4. A method for preparing sodium-doped gallium nitride, characterized in that: The following steps are involved: S1, grinding and mixing melamine, a benzene solution of gallium trichloride and sodium nitrate in a fume hood to obtain a mixture A-2, wherein n(melamine)=n(gallium trichloride)+n(sodium nitrate), n represents the amount of substance, and the amount ratio of gallium trichloride to sodium nitrate is (90–97.5):(10–2.5); S2, transferring the mixture A-2 into a crucible and then into a tube furnace; S3, heating the tube furnace to 800°C under nitrogen or argon protection, keeping the temperature for 6 hours, and naturally cooling to room temperature to obtain solid B-2; S4, washing the solid B-2 with distilled water and drying it to obtain sodium-doped gallium nitride powder.

5. The method for preparing sodium-doped gallium nitride according to claim 4, characterized in that: In step S1, the molar ratio of gallium trichloride to sodium nitrate is 95:

5.

6. The method for preparing sodium-doped gallium nitride according to claim 4 or 5, characterized in that: In step S3, the heating rate of the tube furnace is 2-10°C min -1 ; In step S4, the drying temperature is 60-100°C and the drying time is 4-12h.

7. A lithium-doped gallium nitride powder, characterized in that: The lithium-doped gallium nitride is obtained by the preparation method of any one of claims 1 to 3.

8. A sodium-doped gallium nitride powder, characterized in that: The sodium-doped gallium nitride is obtained by the preparation method of any one of claims 4 to 6.

9. An application of the lithium-doped gallium nitride powder according to claim 7 or the sodium-doped gallium nitride powder according to claim 8, characterized in that: Electrode materials used for working electrodes of supercapacitors.

10. A method for preparing a working electrode, characterized in that: The following steps are involved: Take appropriate amounts of gallium nitride powder, acetylene black and polyvinylidene fluoride, transfer them to an agate mortar, add appropriate amounts of N-methylpyrrolidone, grind them thoroughly, and prepare a slurry, wherein the gallium nitride powder is the lithium-doped gallium nitride powder according to claim 7 or the sodium-doped gallium nitride powder according to claim 8, and the mass ratio of gallium nitride powder, acetylene black and polyvinylidene fluoride is 8:1:1, The slurry was evenly coated on the current collector, and then placed in a vacuum drying oven and dried at 80 °C for 12 h to obtain a working electrode, wherein the loading amount of active material in the working electrode was 2.5-10 mg cm -2 , the active material is lithium-doped gallium nitride or sodium-doped gallium nitride.